IMPLEMENTATION OF THE MERIT SYSTEM IN TALENT MANAGEMENT FOR SCHOLARSHIP SELECTION AT THE DIRECTORATE GENERAL OF BUDGET, MINISTRY OF FINANCE REPUBLIC OF INDONESIA - Randy Praharsa; Haerul Saleh (DIA: Jurnal Administrasi Publik, 2025)
The merit system must be implemented in all aspects of government organizations, both at the central and regional levels, including in human resource development by ensuring equal and objective opportunities for all state apparatus. This study aims to identify the implementation of the merit system in talent management for scholarship selection at the Directorate General of Budget, Ministry of Finance. Through a case study, this research examines how well merit principles such as fairness, transparency, objectivity, and accountability have been applied in the selection process. The results of this study are expected to contribute to improving the quality of governance, particularly in human resource management through the talent management program for scholarship selection.